The Improvement of LEACH Algorithm in Wireless Sensor Networks - Dong, Shujuan; Li, Cong (International Journal of Online and Biomedical Engineering (iJOE), 2016)
This paper covers a novel routing algorithm called Multi-Group based LEACH (MG-LEACH) that has been utilized the redundant deployed sensor nodes to improve the network life time. It has been suppressing the correlated data gathered by the sensor nodes by monitoring the similar event. Thus reduces not only the data transmission inside the clusters but also conserve the energy of deployed sensor nodes consequently improve the overall network lifetime. This is a simple idea that has been implemented over LEACH protocol however it is valid for almost all clustering based routing algorithms/protocols specially those variants based upon frame work of LEACH. The proposed routing algorithm has been simulated using MATLAB to verify the efficiency in enhancing network life time. A critical evaluation of routing algorithm is conducted to determine the relevance and applicability in increasing network life time. Simulation results confirmed that it has performed better than LEACH and enhanced network life time up to approximately 90%.